النخلة ودلالاتها لدى البونيين - سعيدي, سليم (جامعة الوادي - University of Eloued, 2022)
تعتبر النخلة من أهم الأشجار المثمرة التي اكتسبت مكانة هامة في حياة الشعوب السامية القديمة، وخصوصا لدى البونيين، لأهميتها الغذائية وفوائدها المتعدّدة في حياتهم اليومية، إذ استخدموا جذوعها وسعفها في بناء البيوت وصناعة بعض الحاجات كالسلال والحبال... كما سجّلت هذه الشجرة حضورا كبيرا في المجالين الديني والرمزي، فكانت رمزا ملازما لبعض الآلهة وكشجرة مقدّسة ترمز للثروة والخصوبة وتجدّد الحياة، وهذا ما تؤكّده الكثير من اللقى المادية كالأنصاب والنقود والجعارين والأواني الفخارية التي برزت عليها . The palm tree is regarded to be one of the most significant trees due to its fruitulness. It obtained an important position in the acient Semitic peoples lives , especially among the Punic because if its nutritionary importance and aslo the various benefits in their daily lives. They use dits trunks and fronds in building homes and making some needs such as baskets and ropes… The palm tree marked its presence in the relgious and symbolic scops, i twas also a symbol associated with some gods and as a sacred tree symbolizing wealth, fertililty and the renwal for life. This fac twas confirmed by many archaeologiocal remains such as monuments, coins, scarabs and the pottery pots that made the palm tree facade on it.
مقال
Keywords: النخلة؛ الدلالة؛ البونيين؛ الأنصاب؛ الجعارين; The palm, Significance, the Punics, monuments, scarabs